Components of basic feeding rule for infants aged 6-24 months: a scoping review - Haryanti, Fitri; Andarwati, Fitriana; Risnawati, Hani; Lusmilasari, Lely; Hartini, Sri (International Journal of Public Health Science (IJPHS), 2024)
Introducing complementary foods at six months helps supplement nutrients and address potential eating challenges in infants. Childhood eating difficulties can contribute to growth issues. This scoping review aimed to identify the components of feeding rules for infants aged 6-24 months. A systematic search of three electronic databases yielded 5,174 abstracts, with 18 complete articles assessed for eligibility. After eliminating 8 articles, 10 met the criteria. The feeding rules comprise three main components: schedule, environment, and procedure. Adhering to these basic rules can enhance a child's growth rate and reduce the risk of failure to thrive. Responsive feeding is closely linked to these rules, categorized based on feeding schedule, procedures, and environment. Hence, it is crucial for healthcare professionals to provide counseling on the fundamental principles of complementary feeding.